Seed Diversity Five Species of Chili (Capsicum spp.) Based on Morphological Characters and Seed Viability: Keanekaragaman Benih Lima Spesies Cabai (Capsicum spp.) Melalui Karakter Morfologi dan Viabilitas Benih - Undang; Muhamad Syukur; Yudiwanti Wahyu; Abdul Qadir; Siti Marwiyah; Punjung Medaraji Suwarno (Jurnal Hortikultura Indonesia, 2025)
Chili seeds have a lot of diversity and are a cultivation success. Identification of chili seed diversity and seed viability testing is needed as one step in assembling varieties and providing quality seeds. The objective of this study was to obtain information on seed shape, beak protrusion, 1000-seed weight, and seed viability. The study was conducted on 63 chili genotypes from 5 species (Capsicum annuum, C. frutescens, C. chinense, C. baccatum, and C. pubescens) in February-July 2023 at the IPB Seed Science and Technology Laboratory, using a randomized complete block design with 3 replications. Observations include the morphological and physiological properties of chili seeds. Chili seeds are generally yellowish white with a beak protrusion, except C. pubescens (black color, no beak protrusion), kidney-shaped seeds (C. annuum), oval (C. baccatum), teardrops (C. frutescens), D-shaped (C. pubescens), circular with a fish mouth (C. chinense). The chili species observed had various sizes of 1000-seed weight (light (5.68 g). Genetic diversity of germination, maximum growth potential, vigor index, growth rate, and growth simultaneity were categorized broadly, while normal dry weight of sprouts, growth rate, and 1,000 seed weight were categorized narrowly. Seed size did not affect the percentage of seed germination. The C.pubescens species had different seed characteristics from other Capsicum species, while the C.annuum species had similarities with C.frutescens, C.chinense, and C.baccatum.Keywords: chili, diversity, morphology, seeds, species